EUROPEAN PRACTICE OF SOLVING ISSUES OF EFFECTIVE FUNCTIONING OF SURFACE DRESSING OF PAVEMENT. СOMPLIANCE OF SURFACE DRESSING CHARACTERISTICS WITH TECHNICAL CONDITIONS OF DSTU EN 12271:2021 (EN 12271:2006, IDT) - Ivan Kopynets; Mykola Stulii; Tetiana Protopopova (Дороги і мости, 2022)
Introduction. The wearing course of a road pavement is in complicated operational conditions in combination with adverse weather and climatic factors that are characteristic of the country for most of the year. These factors make high demands on the wearing course, in particular arranged by the method of a surface dressing. European practice of solving these issues is based on the provisions of a set of standards that can serve to solve the problems of effective functioning of a surface dressing on roads in Ukraine.